Peak torque angle, acceleration time and time to peak torque as additional parameters extracted from isokinetic test in professional soccer players: a cross-sectional study - Germano Maciel, D.; Figueiredo Dantas, G. A.; Santos Cerqueira, M.; Mendonça Barboza, J. A.; Vieira De Alencar Caldas, V.; Cavalcanti Matias de Barros, A.; Romeno Varela, R.; Helps Magalhães, D.; Hérickson de Brito Vieira, W. (Sports Biomechanics, 2023)
This study investigated additional and traditional variables from isokinetic test of thigh muscles in soccer players across different field positions. One hundred and eighty-nine athletes performed maximal concentric isokinetic knee contractions on dominant (DL) and non-dominant limb (NDL) at 60º/s and 240º/s. The additional outcomes peak torque angle (AngPT), acceleration time (AcT) and time to peak torque (TPT) and traditional outcomes Peak torque (PT), total work (TW) and power (Pw) were extracted from the exam. Goalkeepers (GK), side backs (SB), central backs (CB), central defender midfielders (CDM), central attacking midfielders (CAM) and forwards (FW) were considered. Comparisons between limbs and positions demonstrated that SB extensors of the DL presented TPT lower (p = 0.006) and AngPT higher (p = 0.011) than NDL at 60°/s. CDM extensors of the DL showed lower TPT at 60°/s (p = 0.003) and 240°/s (p = 0.024). CAM flexors of the DL showed lower TPT (p = 0.026) and AcT (p = 0.021) at 240°/s than NDL. CB, CDM and CAM extensors of the NDL showed higher PT, TW and Pw than DL (p < 0.05). In conclusion, there are muscle imbalances between limbs in SB, CDM and CAM and across different field positions.